An introduction to Contextual embeddedness of entrepreneurship - Xheneti Mirela; Costa Sílvia; Heinonen Jarna; Kurczewska Agnieszka (Edward Elgar Publishing, 2025)
The contextual turn in the field of entrepreneurship means it is crucial fpr scholars to integrate into their research the multifaceted contexts in which entrepreneurship is embedded. This insightful book explores the different spatioal, social, digital, institutional and policy contexts for entrepreneurship and investigates their relevance for entrepreneurship thoery and practice.
Featuring cutting-edge research, this book presents a wide range of theoretical approaches undertaken to study entrepreneurial behaviour and processes, analysing their relevance to policy and practice. Chapters examine these approaches through the lens of specific issues and circumstances related to digital, edtech, social, international ands peripheral entrepreneurship, exploring diverse perspectives and illustrating how different contexts shape entrepreneurial activity and its outcomes.
Contextual Embeddeness of Entrepreneurship: Frontiers in European Entrepreneurship Research